Towards A Mutualism Performance Audit on Local Governments Between Auditor and Community - Windu Wibisono; Roy V. Salomo; Chandra Wijaya (STISIPOL Raja Haji, 2021)
BPK as Supreme Audit Institution (SAI)has been massively conduct financial audit on local government in Indonesia. Quality of financial statement is also upgraded, known from the improvement of BPK’s opinion. However, quality, transparency and accountability of local government are still far from public expectation. This paper shows the importance of public needsto improve the performance of local governments by support from BPK especially their performance audit. This paper will discuss the development of performance audit in BPK especially at the local government. This paper uses the analysis of Baimyrzaeva and Kose (2014) that states about role of SAI in collaboration with the community will be mutually beneficial to both parties by focusing on the areas that received great attention from the public and reacting well. This paper results show that the quantity of performance audits of local governments continue to rise. However, most of the audit they are stand-alone and need to led to the outcome-oriented for the communities. This paper discusses the case of performance audit of the provision of water as a performance audit that successfullygive more impact on communities in local government. To be more impactful performance audit, this paper proposes the model of participatory audit, especially when BPK planning the audit.